Qualidade de peixes tilápia (oreochromis niloticus) e serra (scomberomorus brasiliensis) comercializados em feiras livres e mercados públicos - Oliveira Neto, José Tavares de (Universidade Federal Rural do Semi-Árido, 2018)
Due to its high perishability, the fish requires a peculiar attention, since an inadequate manipulation exposes the food to contaminants that can compromise its quality and to pose risks to the population that consumes it. The objective of this study was to evaluate the sensory, microbiological and physicochemical quality of the fish species: Nile tilapia (Oreochromis niloticus) and saw (Scomberomones brasiliensis), as well as hygienic-sanitary conditions of commercial establishments of this fish. For this, an observational study, based on RDC nº 216/04 of the current legislation on the conditions of the physical facilities and the manipulation of its merchants of eight establishments was carried out through a checklist. Microbiological (Staphylococcus coagulase positive, coliforms at 45° C and Salmonella spp.) and physico-chemical analyzes (pH, temperature, titratable acidity, lipid oxidation, determinations of volatile nitrogen bases, moisture, lipids, mineral matter and total protein). Regarding the hygienic-sanitary conditions of the places of sale, none of the establishments presented 100% compliance with ANVISA RDC nº 216/04, in at least one of the three hygiene criteria evaluated (marketing environment, manipulators and utensils). In relation to the fish samples, in their sensorial attributes related to appearance, odor and texture, these were in conformity with the standards recommended by Brazilian legislation, in 82% and 75% for the fishes saw and tilapia, respectively, in the aspects of analysis of freshness. For the microbiological conditions, in the Staphylococcus coagulase positive count, it was found non-compliance with the legislation in 79,2% and 100%, as well as for coliforms at 45° C with 8,3% and 12,5%, of the analyzed samples, for the sawfish and the tilapia, respectively. The presence of Salmonella spp. in none of the species. As for the physical-chemical aspects, all the samples were within the limits recommended by the legislation. Therefore, it can be concluded that, sales sites need improvements in their physical structure, as well as training for their manipulators. Precarious fish species are responsible for contamination and consumer health risk. However, the Nile tilapia species from aquaculture presented lower freshness aspects than the marine fish species
Keywords: Manipulação; Frescor; Pescado; Qualidade microbiológica; Manipulation; Freshness; Seafood; Microbiological quality; CIENCIAS AGRARIAS::ZOOTECNIA